The efficacy of orally administered L-carnitine in alleviating ovarian dysfunctions has laid the foundation for targeted in vivo use: a study employing self-control and propensity score matching - Zhao, Wenjie; Liu, Kunkun; Zhang, Yuhua; Sun, Pingping; Zeringue, Ernest; Meng, Li; Ma, Huagang (Frontiers in Endocrinology, 2024)
Objective:This study aimed to evaluate the effectiveness of oral L-carnitine administration in patients after treatment failure to lay the groundwork for targeted in vivo use.Methods and materials:A total of 515 IVF patients undergoing subsequent cycles were included after applying exclusion criteria. They were divided into a control group of 362 patients and a study group of 153 patients who received oral L-carnitine until oocyte retrieval.140 patients were matched according to maternal age,infertility duration,body mass index (BMI), day three top-quality embryos rate, by propensity score matching (PSM). The study investigated the relationship between L-carnitine treatment and in vivo oocyte maturation, normal fertilization, and subsequent embryo development.Results:Following PSM, initial differences in BMI and Day3 top-quality embryo rate between groups were nullified,we created two comparable cohorts with highly similar characteristics.In the subsequent cycles,the study group showed significant improvements in in vivo oocyte maturation rate at retrieval (p=0.002), normal in vitro fertilization rate (p=0.003), blastocyst formation rate (p=0.003), and usable blastocyst rate compared to controls. Although there was no significant difference in the top-quality embryo rate on Day 3, the study group showed a 10% increase in the upper quartile (55.35% vs. 66.67%). The cumulative clinical pregnancy and live birth rates showed a significant improvement (59.82% vs. 68.42%,p=0.004，47.41% vs. 59.80%, p=0.002). Furthermore, self-control analysis revealed substantial enhancements (p<0.001) in all outcome measures following L-carnitine administration, resulting in the birth of 74 healthy neonates without congenital anomalies.We theorized that daily oral intake of L-carnitine before oocyte retrieval could boost oocyte quality and embryonic development, thus improving IVF outcomes.Ongoing investigations hold the potential to offer valuable insights into the applications and mechanisms underlying the therapeutic effectiveness of L-carnitine.